Comparison between evaporative cooling and a heat pipe assisted thermal loop for a commercial wind tower in hot and dry climatic conditions - Calautit, John Kaiser; Chaudhry, Hassam Nasarullah; Hughes, Ben Richard; Ghani, Saud Abdul (Applied energy, 2013)
► Incorporating heat pipes within a roof mounted wind tower to meet internal comfort. ► Multiphase flow behaviour investigation on water and ethanol as heat pipe fluids. ► Comparison was established between a heat pipe integrated wind tower and evaporative cooling method. ► The proposed system consisting of heat pipes was capable of reducing the air temperatures by 12–15K. ► Height was not a factor for the proposed design, making it highly viable for commercial wind towers. Increasing focus on reducing energy consumption has raised public awareness of renewable energy resources, particularly the integration of natural ventilation devices in buildings such as wind towers. The purpose of this paper was to compare the traditional evaporative wind tower technique with a proposed wind tower system consisting of heat pipes. Computational Fluid Dynamics (CFD) was used to develop a numerical model of a wind tower system and simulate the air flow pattern around and through the device. A baseline heat exchanger section containing cylindrical heat pipes was constructed to simulate the multiphase flow behaviour of two-phase heat pipe working fluids including water and ethanol. Heat transfer rate was obtained at 113 and 106W for water and 72 and 116W for ethanol respectively. The second part of the study incorporated the cylindrical heat pipes within the control domain of a roof-mounted wind tower, highlighting the potential to achieve minimal restriction in the external air flow stream while ensuring maximum contact time, thus optimizing the cooling duty of the device. A comparison was established with the conventional evaporative cooling methodology. The proposed cooling system consisting of heat pipes was capable of reducing the air temperatures by 12–15K, depending on the configuration and operating conditions. The technology presented here is subject to IP protection under the QNRF funding guidelines.